PREPARATION OF SILVER NANO-PARTICLES IN BENZENE SOLVENT BY LASER ABLATION METHOD - ABAULLAH, MUHAJ TALIB (Journal of Duhok University, 2023)
Nd-yag laser with wavelength (λ) =1064nm and energy 1100 mJ was used to prepare Ag nano particles in aromatic solvent benzene for the first time in this work according to our knowledge. UV–Vis spectroscopy, X-ray diffraction (XRD), (EDX), TEM, FTIR, Photoluminescence measurement, and Raman shift were used to examine the optic, structural, as well as morphological features of Ag Nano particles. According to XRD patterns, the synthesized Ag NPs exhibit a nanocrystalline and cubic (FCC) structure. The direct optical energy gap of Ag NPs discovered to be within the range of (2.8) eV. The Photoluminescence emission spectra and excitation spectra of Ag the emission peak fixed around 380 and 430 nm respectively. When the findings from the experiment are compared to those from the reference sample, it becomes clear that benzene has substantially higher nanoparticle production efficiency and smaller particle sizes